Pengaruh Beban Kerja dan Disiplin Terhadap Komitmen Pegawai pada Dinas Pendidikan Pemuda dan Olahraga Kebupaten Solok - Siti Rukmana; Nurhayati Nurhayati; Afni Yeni (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This study aims to analyze the effect of workload and discipline on employee commitment at the Solok district youth and sports education office. The sample in this study were 79 respondents with the total sampling method. Based on the results of multiple linear regression analysis of the variables Workload and Discipline on Employee Commitment with a value of Y = 14.413 + 0.259(X1) + 0.303 (X2) + e. From the t test conducted on the X1 variable, namely Workload with a t-count value smaller than t-table 1.735 > 1.992, which means that the Workload variable has no effect on Employee Commitment, while the X2 variable, namely Discipline, obtains a greater t-count value from t-table 3, 832 > 1.992 which means Discipline affects Employee Commitment. While the results of the f-test analysis obtained the f-count value is greater than the f-table, namely 10.860 > 3.12, which means that Workload and Discipline together affect Employee Commitment.